Dynamic time warping to quantify age distortion in firn cores impacted by melt processes - Cedric J. Hagen; Joel T. Harper (Annals of Glaciology)
As warming intensifies across the Greenland ice sheet, an increasing number of shallow coring and radar studies are targeting the melt-impacted firn column to investigate meltwater processes. Highly inhomogeneous infiltration and refreezing, however, redistributes mass, distorting age–depth relationships and confounding comparisons between different cores. Here, we utilize a dynamic time warping algorithm for time series alignment to investigate and quantify the heterogeneous impact of melt processes on nine closely spaced (within 50 m) firn core-density profiles. The 10 m cores were collected relatively high in Greenland's percolation zone, where melt alteration is minimal compared to lower elevation. Our analysis demonstrates the effectiveness of dynamic time warping as a tool for assessing heterogeneity between ice core records. We find that the optimal alignment of density profiles in the nine cores requires vertical stretching and compression of individual profiles, ranging from, on average, <1 to ~16% of the core lengths. We identified four depth zones of mass redistribution that appear to coincide with observed ice layers. Further, ~75% of density measurements from each core do not align with an age model-derived density profile that assumes no mass redistribution of meltwater, indicating the pervasive impact of melt processes.